Combination of Prenatal Gentle Yoga with Dhikr to Reduce The Anxiety Level of Pregnant Women - Nurhidayah, Nurhidayah; Gani, Nurul Fadhilah; Muthahharah, Muthahharah; Hasnah, Hasnah (Diversity: Disease Preventive of Research Integrity, 2024)
Anxiety in pregnant women should receive special attention. This psychological problem can even continue into the postpartum period, contributing to the emergence of baby blues and even postnatal depression. The level of anxiety in pregnant women can be minimized with non-pharmacological measures such as prenatal gentle yoga. This study aims to determine the effect of gentle yoga therapy and prenatal dhikr on the anxiety level of pregnant women in the Makassar Urban Area. This research used a pre-experimental design with a one group pretest and posttest design, with a sample of 25 pregnant women. This research uses prenatal gentle yoga and dhikr therapy interventions to reduce anxiety during pregnancy. Univariate analysis was carried out to obtain information regarding sample characteristics such as age, education, parity and gestational age. Bivariate analysis was carried out to find out what happened before and after prenatal gentle yoga and dhikr therapy. The results of the study showed that there was a difference in the level of anxiety of pregnant women (p= 0.000) before and after receiving gentle yoga and dhikr prenatal therapy intervention. In this study, gentle yoga prenatal therapy combined with dhikr was proven to be able to reduce anxiety levels in pregnant women, so that education and socialization can be given to pregnant women so that it becomes a habit.